Program Inisiasi Kelompok Siap Tanggap (Siaga) Cedera pada Siswa di SMPN 1 Kalisat - Eky Madyaning Nastiti; Rida Darotin; Indri Dwi Hapsari (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
Students get injuries because of cuts, bleeding and sprains. Injuries occur with activities carried out such as academic learning in the form of sports. First aid is emergency care or treatment before medical help can be given to prevent serious problems. The aim of PKM is to form a group of injury prepared students so that they will later become first responder initiators. The method is through a series of health education and training using short films in regional languages at SMPN 1 Kalisat. The results of the activity showed that there was an increase in students' knowledge from those previously in the inappropriate category. After the activity was carried out in the very appropriate category. Health Education Activities are the first step in initiating students to be prepared for injuries. This initiation is to form extracurricular PMR which has not yet been formed at school.